Improving Homework Performance Among Children with ADHD: A Randomized Clinical Trial - Merrill, Brittany M. (J Consult Clin Psychol, 2016)
OBJECTIVE: Evidence indicates that children with Attention Deficit Hyperactivity Disorder (ADHD) experience acute and prolonged academic impairment and underachievement including marked difficulty with completing homework. This study is the first to examine the effects of behavioral, psychostimulant, and combined treatments on homework problems, which have been shown to predict academic performance longitudinally. METHOD: Children with ADHD (ages 5-12, N = 75, 71% male, 83% Hispanic/Latino) and their families were randomly assigned to either behavioral treatment (homework-focused parent training and a daily report card; BPT+DRC) or a waitlist control group. Children also participated in a concurrent psychostimulant crossover trial conducted in a summer treatment program. Children's objective homework completion and accuracy were measured as well as parent-reported child homework behaviors and parenting skills. RESULTS: BPT+DRC had large effects on objective measures of homework completion and accuracy (Cohen's ds from 1.40, to 2.21, ps < .001). Other findings, including unimodal medication and incremental combined treatment benefits, were not significant. CONCLUSIONS: Behavioral treatment focused on homework problems results in clear benefits for children's homework completion and accuracy (the difference between passing failing, on average) whereas long-acting stimulant medication resulted in limited and largely non-significant acute effects on homework performance.